Why do patients with stroke not receive the recommended amount of active therapy (ReAcT)? Study protocol for a multisite case study investigation. Issue 8 (25th August 2015) - Clarke, David J; Tyson, Sarah; Rodgers, Helen; Drummond, Avril; Palmer, Rebecca; Prescott, Matthew; Tyrrell, Pippa; Burton, Louisa; Grenfell, Katie; Brkic, Lianne; Forster, Anne
Abstract : Introduction: Increased frequency and intensity of inpatient therapy contributes to improved outcomes for stroke survivors. Differences exist in the amount of therapy provided internationally. In England, Wales and Northern Ireland it is recommended that a minimum of 45 min of each active therapy should be provided at least 5 days a week provided the therapy is appropriate and that the patient can tolerate this. Sentinel Stroke National Audit Programme (2014) data demonstrate this standard is not being achieved for most patients. No research been undertaken to explore how therapists in England manage their practice to meet time-specific therapy recommendations. The ReAcT study aims to develop an in-depth understanding of stroke therapy provision, including how the guideline of 45 min a day of each relevant therapy, is interpreted and implemented by therapists, and how it is experienced by stroke-survivors and their families. Methods and analysis: A multisite ethnographic case study design in a minimum of six stroke units will include modified process mapping, observations of service organisation, therapy delivery and documentary analysis. Semistructured interviews with therapists and service managers (n=90), and with patients and informal carers (n=60 pairs) will be conducted. Data will be analysed using the Framework approach. Ethics and dissemination: The study received a favourable ethical opinion via the National Research Ethics Service (reference number: 14/NW/0266). Participants will provide written informed consent or, where stroke-survivors lack capacity, a consultee declaration will be sought. ReAcT is designed to generate insights into the organisational, professional, social, practical and patient-related factors acting as facilitators or barriers to providing the recommended amount of therapy. Provisional recommendations will be debated in consensus meetings with stakeholders who have not participated in ReAcT case studies or interviews. Final recommendations will be disseminated to therapists, service managers, clinical guideline developers and policymakers and stroke-survivors and informal carers.